High‐resolution satellite imagery meets the challenge of monitoring remote marine protected areas in the Antarctic and beyond. Issue 4 (31st March 2022) - LaRue, Michelle; Brooks, Cassandra; Wege, Mia; Salas, Leonardo; Gardiner, Natasha
Abstract: Remote, high‐latitude oceans can prove challenging for the designation and implementation of marine protected areas (MPAs), partly due to issues in monitoring inaccessible localities and large spatial scales. A lack of protection combined with damage from growing human activities has contributed to the degradation of some of the Earth's richest marine biodiversity and highlights the urgent need to support improved marine conservation. High‐resolution satellite imagery (VHR; 0.3–0.6 m spatial resolution) provides a much‐needed tool for monitoring sentinel species in remote oceans, which would strengthen current and future MPA research and monitoring programs across the globe. This perspective specifies how recent advances in VHR studies have contributed to knowledge regarding occurrence, habitat suitability, and abundance of mesopredators in the Southern Ocean. We demonstrate how knowledge gained through VHR offers a cost‐effective and easily accessible method for collecting previously unobtainable data to inform a representative network of Southern Ocean MPAs, and how the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) could utilize this technology. As VHR and automated detection algorithms continue to improve, we showcase a promising opportunity to use these methods to complement current research and monitoring efforts, thus strengthening MPA efforts in the Southern Ocean and beyond.